An Experimental Investigation on Effect of B4C/CeO2 Reinforcements on Mechanical, Fracture Surface and Wear Characteristics in Al7075 Hybrid Metal Matrix Composites - Dr. Ravikumar M; Hanumanthe Gowda; Umesh G L; Raghavendra S; Darshan S M; Shivakumar M M; Santhosh Somashekar (International Journal of Integrated Engineering, 2024)
Stircasting method is commonly used to efficiently produce high-grade Metal Matrix Composites (MMCs). In the current study, we produced hybrid materials by altering the weight percentages of B4C, which were 2%, 4%, 6%, and 8%, while maintaining a constant weight percentage of 5% for Cenosphere. Following that, we performed examinations of microstructure, hardness, and tensile properties on both the as-cast materials and the hybrid composites. The microstructural analysis unveiled a consistent dispersion of reinforced particles throughout the base matrix, which was observed in both the as-cast and hybrid composite samples. Highest hardness of 86.55 VHN is achieved for the 8% B4C + 5% cenosphere reinforced MMCs. The maximum tensile strength of 180.58 MPa is obtained for 6% B4C + 5% cenosphere reinforced MMCs. Minimum wear loss is observed in the 6% B4C + 5% cenosphere reinforced MMCs. The ductility of the hybrid composite is decreased as the amount of reinforcement was increased. The tensile fractured sample shows the voids, micro-cracks and particles pullouts. It indicates the strong adhesion between the reinforcements and the matrix material, with bonding influenced by the reinforcement geometry and grain size. The wornout surfaces of the as-cast show the deep grooves, delamination and ploughs on the wear directions. However, hybrid MMCs micro-graphs indicate the deep grooves, particles pullouts and voids in the wear directions. It is due to the high hard reinforcement’s presence in the matrix and resists wear of MMCs.